If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 = 5x + 8 Reorder the terms: -3 + 7x = 5x + 8 Reorder the terms: -3 + 7x = 8 + 5x Solving -3 + 7x = 8 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 7x + -5x = 8 + 5x + -5x Combine like terms: 7x + -5x = 2x -3 + 2x = 8 + 5x + -5x Combine like terms: 5x + -5x = 0 -3 + 2x = 8 + 0 -3 + 2x = 8 Add '3' to each side of the equation. -3 + 3 + 2x = 8 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 8 + 3 2x = 8 + 3 Combine like terms: 8 + 3 = 11 2x = 11 Divide each side by '2'. x = 5.5 Simplifying x = 5.5
| -9(6-u)-2u=-10 | | 5(3)-4=11 | | 6x-7=10x+5 | | 5(-1.4)-4=11 | | (y+9)= | | 5=-x/-2+6 | | 27-6d=7t+4d | | 5=-x/2+6 | | 10-6x=11x-24 | | -28-3x= | | 9y+5(4-9)=39 | | 70-4x= | | 3x+27-8=67 | | 8-8x=68-29x | | -4x-9=7x+2 | | 2-3x=3x-22 | | (n+3)(n^2+3n+5)= | | m=64 | | 3x+14=68 | | -x+5=5x-13 | | x^2+2mx+3m-2=0 | | (3y+2y^2+y^3)+(-6y-8y^2+5y^3)= | | 6x+16=4x+68 | | (5y-2)(2y+6)= | | -6x+16=2x+8 | | 5(3w-2)-10w=-2(3w-10) | | -6+16=2x+8 | | (3x^2-6y^2+9xy)-(6xy-3y^2)= | | 5x+4x+9=67 | | (x-3)^2/3=25 | | -x-8=10 | | n+17=20 |